The Influence of Political Decisions on Bitcoin Prices with Good Corporate Governance as A Moderating Variable - Rieneke Ryke Kalalo; Hugo Prasetyo Winotoatmojo; Wiljan Atfentia Kotngoran; Heppi Syofya; I Gusti Made Riko Hendrajana (Yayasan Inovasi Kemajuan Intelektual, 2025)
This study examines the impact of political decisions on Bitcoin price volatility, with Good Corporate Governance (GCG) as a moderating variable. While Bitcoin is often perceived as a decentralized asset independent of government control, empirical evidence suggests that regulatory announcements, geopolitical tensions, and national legal tenders significantly influence market sentiment and price fluctuations (Aditya & Wijaya, 2024). This research utilizes a quantitative approach with secondary data from 2020 to 2025, capturing major political shifts and global economic policies. The analysis focuses on how the quality of corporate governance within major institutional holders of Bitcoin moderates the transmission of political shocks to asset prices. Preliminary findings indicate that political decisions regarding restrictive regulations tend to decrease prices, whereas institutional adoption backed by strong GCG frameworks serves as a buffer against extreme volatility. This study contributes to the literature on digital asset management and provides strategic insights for investors and policymakers in navigating the complex intersection of global politics and financial technology.